Spinal subarachnoid hemorrhage complicating oral anticoagulant therapy - Cihangiroglu, M; Bulut, S; Nayah, S (Elsevier Sci Ireland Ltd, 2001)
Spinal subarachnoid hemorrhage (SAH) is rare clinical entity possible owing to the diluting and fibrinolytic effects of cerebrospinal fluid (CSF). When it occurs, it is most commonly encountered in the thoracic segment of the subarachnoid space. We present a case of a 50-year-old man who sustained spinal SAH in the cervical and thoracic segments related to anticoagulant therapy. He progressed to significant neurological deficit since he was inoperable, an observation that supports the need for decompression surgery. We should be aware of potential hematomyelia should a patient on anticoagulant therapy develop neurological symptoms localized to the spinal cord. When available, magnetic resonance (MR) imaging is the modality of choice to diagnose and follow-up spinal SAH. (C) 2001 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: spine; subarachnoid hemorrhage; magnetic resonance imaging